Growth, ferulic acid synthesis, and histochemistry of calli of Pouteria caimito (Ruiz & Pav.) Radlk under different light qualities - Melo, Anielly Monteiro (2020)
Interest in harnessing biological processes for the production of bioactive compounds from natural sources has increased considerably. The manipulation of light quality in callus culture is considered a promising strategy for in vitro metabolite production. The objective of this study was to investigate the influence of light quality on the growth, histochemistry, and ferulic acid production of callus cultures of P. caimito. For in vitro callus induction, 1-cm2 leaf fragments were cultured in 50% MS medium supplemented with 2,4-dichlorophenoxyacetic acid and benzylaminopurine in the absence or presence of light (white, blue, green, yellow, or red). Methanol extraction was performed with partitioning of the extract and subsequent quantification of ferulic acid using a liquid chromatograph coupled to a mass spectrometer. The presence of light promoted greater growth than the absence of light. In the interaction between light quality and culture time, linear biomass growth until 28 days was observed under yellow, red, and blue lights and in the dark. The highest callus biomass values were observed under yellow and red lights. The histochemical tests showed the presence of phenolic compounds, alkaloids, flavonoids, and terpenes. The exposure of calli cultured under white light to different light qualities and culture times did not result in significant differences in the concentration or yield of ferulic acid.